2019
DOI: 10.1029/2019gc008312
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Impacts of the 1997–1998 Bleaching Event on the Growth and Resilience of Massive Porites Corals From the Central Red Sea

Abstract: This study investigates the impact of extreme heat wave events on long‐lived massive corals (Porites spp.) from the central Saudi Arabian Red Sea using trace element (Sr/Ca, Li/Mg, Mg/Ca, U/Ca, B/Ca, and Li/Ca) records preserved in the coral skeleton for the period between 1992 and 2012. Prior to 1998, the trace element records show strong correlations with sea surface temperature. However, during the prolonged high temperature phase associated with the 1998 El Niño event, the seasonal trace element signals we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
25
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 80 publications
8
25
1
Order By: Relevance
“…While this evidence for thermal acclimatization is limited by the absence of intrasite reproducibility of these TE signatures, as well as supporting environmental data (water quality, light, etc. ), we do note its consistency with previous research that has shown increased thermal resilience in corals following their repeated exposure to marine heat waves (DeCarlo et al, ; D'Olivo et al, ; Guest et al, ; Maynard et al, ). For example, DeCarlo et al () recently showed a reduced proportion of stress bands in Porites spp.…”
Section: Discussionsupporting
confidence: 90%
“…While this evidence for thermal acclimatization is limited by the absence of intrasite reproducibility of these TE signatures, as well as supporting environmental data (water quality, light, etc. ), we do note its consistency with previous research that has shown increased thermal resilience in corals following their repeated exposure to marine heat waves (DeCarlo et al, ; D'Olivo et al, ; Guest et al, ; Maynard et al, ). For example, DeCarlo et al () recently showed a reduced proportion of stress bands in Porites spp.…”
Section: Discussionsupporting
confidence: 90%
“…Corals themselves can shed light on past SST variability, though, since the trace-element geochemistry of their skeletons is sensitive to temperature ( Corrège, 2006 ; Nurhati, Cobb & Di Lorenzo, 2011 ). Previous analyses of temperature proxies in coral skeletal cores from Abu Shosha and Shi’b Nazar showed some of the highest summer temperature peaks in the early 2000s ( D’Olivo et al, 2019 ; see also Murty et al, 2018 ), broadly consistent with the satellite data, especially OI-SSTv2.…”
Section: Discussionsupporting
confidence: 75%
“…I can conclude with 95% confidence that no prior event reached this severity since 1934. Skeletal geochemistry of Abu Shosha Porites was also perturbed during this event, indicative of disruptions to the normal calcification process ( D’Olivo et al, 2019 ). The complete absence of stress bands in cores outside of Abu Shosha suggests this event may have been restricted to nearshore environments.…”
Section: Discussionmentioning
confidence: 99%
“…Given the high concentrations of Mn present in the coral tissue layer, which often covers ∼1 year of skeletal growth, it is possible that the incorporation of Mn into the coral skeleton occurs over the course of several months, whether during thickening, formation of tissue inclusions, or adsorption onto the skeleton following tissue decay. Such biosmoothing may be exacerbated during the El Niño‐related warming that follows WWEs, given sufficient stress to impact calcification rates (D'Olivo et al., 2019). However, another possibility is that the morphology of Tarawa's lagoon is very different from that of either Kiritimati or Butaritari.…”
Section: Discussionmentioning
confidence: 99%